Проблематика дистанційного навчання у світі та Україні - Колокольчикова, Ірина Володимирівна; Шокарев, Олександр Миколайович; Kolokolchykova, Iryna; Shokarev, Oleksandr (Запоріжжя : 2024, 2024)
UA: Визначено проблематику дистанційного навчання здобувачів вищої освіти в умовах сьогодення. Досліджено відношення до дистанційного навчання учасників освітнього процесу розвинутих країн та України. Встановлено напрямки покращення мотивації до дистанційного навчання та підвищення ефективності її застосування. EN: The problems of distance learning of higher education students in today’s conditions are defined. The relation to distance learning of participants in the educational process of developed countries and Ukraine has been studied. Directions for improving motivation for distance learning and increasing the effectiveness of its application have been established.
Problems of distance education in the world and in Ukraine
Keywords: дистанційне навчання; інноваційні засоби; комунікаційні технології; мотивація; онлайн-освіта; респонденти; distance learning; innovative means; communication technologies; motivation; online education; respondents